Adaptations in gastrointestinal nutrient absorption and its determinants during pregnancy in monogastric mammals: a scoping review protocol. Issue 2 (9th February 2022) - Overduin, Teunis Sebastian; Page, Amanda J.; Young, Richard L.; Gatford, Kathryn L.
ABSTRACT: Objective: The aim of this review is to characterize the current state of literature and knowledge regarding adaptations of gastrointestinal nutrient absorption, and the determinants of this absorption during pregnancy in monogastric mammals. Introduction: Energy demands increase significantly during pregnancy due to the metabolic demands associated with placental and fetal growth, and the deposition of fat stores that support postnatal lactation. Previous studies have examined anatomical changes within the small intestine, but have focused on specific pregnancy stages or specific regions of the small intestine. Importantly, little is known about changes in nutrient absorption during pregnancy, and the underlying mechanisms that lead to these changes. An understanding of these adaptations will inform research to improve pregnancy outcomes for both mothers and newborns in the future. Inclusion criteria: This review will include primary literature that describes gastrointestinal nutrient absorption and/or its determinants during pregnancy in monogastric mammals, including humans and rodents. Only data for normal pregnancies will be included, and models of pathology and illness will be excluded. Studies must include comparisons between pregnant animals at known stages of pregnancy, and non-pregnant controls, or compare animals at different stages of pregnancy. Methods: The following databases will be searched for literature on this topic: PubMed, Scopus, Web of Science, Embase, MEDLINE, and ProQuest Dissertations and Theses. Evidence screening and selection will be carried out independently by two reviewers, and conflicts will be resolved through discussion with additional members of the review team. Data will be extracted and presented in tables and/or figures, together with a narrative summary.